Catalyst-controlled diastereoselectivity reversal in the formation of dihydropyrans. Issue 28 (22nd March 2018) - Kano, Taichi; Maruyama, Hiroki; Homma, Chihiro; Maruoka, Keiji
Abstract : In dihydropyran synthesis, use of ( S )-3b is crucial for overcoming the inherent trans -selectivity and obtaining unusual cis -adducts with high enantioselectivity. Abstract : An enantioselective synthesis of cis -dihydropyrans as the formal HDA reaction products was achieved through the catalyst-controlled anti -selective conjugate addition of aldehydes to β, γ-unsaturated α-keto esters. The observed unusual cis -selectivity could be attributed to the stabilization of the less favorable transition state for anti -conjugate adducts by the hydrogen bonding between the hydroxy group of the amino diol catalyst and β, γ-unsaturated α-keto esters.